The Impact of Risk Assessment on Juvenile Justice Decision-Making and New Adjudication: An Analysis of Usage and Outcome - Petkus, Amber A. (Youth violence and juvenile justice, 2022)
Juvenile risk and needs assessments (JRNAs) have been the focus of extensive research in the academic literature. Prior studies have primarily focused on the risk-recidivism relationship and establishing predictive validity with juvenile populations. Less investigated is the use of risk and need assessment in practice, including how such tools are used to inform decision-making. This study uses record data encompassing 3,034 youth from a multi-state study to examine dispositional and treatment decisions associated with the Ohio Youth Assessment System (OYAS). Specifically, mediation analyses were conducted to evaluate how current practices align with underlying logic and theory regarding the role of assessments in juvenile justice. Findings reveal varied and complex relationships between assessment scores, case decisions, and recidivism. While risk was generally associated with recidivism, our results suggest juvenile risk and need assessments are inconsistently used to inform case management and placement decisions. Implications for practice and future research are also discussed.